2015
DOI: 10.1021/acsami.5b08042
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Compression ofEscherichia coliK12 Cells under the Effect of TiO2Nanoparticles

Abstract: It has been shown that treatment with titanium dioxide nanoparticles (TiO2 NPs) combined with near-ultraviolet (UV-A) irradiation or in certain dark conditions reduced the numbers of various microorganisms, but the mechanism of this effect remains unclear. In this study to further clarify the mechanism of the antibacterial effect of TiO2 NPs the physiological state of E. coli K12 cells was estimated after incubation with the NPs (0.2 g/L) for different periods of time, with or without UV-A irradiation. Cell in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Of particular concern in the NP literature is the use of bacterial strains which are not typically considered pathogenic or of industrial significance. The most common are K12 strains of E. coli which are commonly used in molecular biology laboratories as expression or cloning vectors(60, 61). Although these strains are convenient, they are engineered strains and typically lack many of the highly evolved and redundant defense mechanism of true pathogens.…”
Section: Sources Of Experimental Variabilitymentioning
confidence: 99%
“…Of particular concern in the NP literature is the use of bacterial strains which are not typically considered pathogenic or of industrial significance. The most common are K12 strains of E. coli which are commonly used in molecular biology laboratories as expression or cloning vectors(60, 61). Although these strains are convenient, they are engineered strains and typically lack many of the highly evolved and redundant defense mechanism of true pathogens.…”
Section: Sources Of Experimental Variabilitymentioning
confidence: 99%
“…Iron can also cause bacterial cell decomposition, 114 and NPs can cause bacterial cells to aggregate, resulting in inactivation due to compression. 115 Physical damage of bacterial membranes is the most important mechanism of the antibacterial activity of graphene. Tu et al 116 investigated the antibacterial molecular mechanisms of graphene nanosheets against E. coli.…”
mentioning
confidence: 99%
“…TiO 2 NPs allow bacterial DNA compression, degeneration, and fragmentation, thereby reducing the physiological activity of genes. 115 The affinity and binding mode of nanotitanium dioxide and DNA were predicted by molecular docking, which indicated that TiO 2 NPs targeted DNA rich in G-C. 130 In addition, whole-genome analysis can be used to characterize the molecular mechanisms of bacterial apoptosis.…”
mentioning
confidence: 99%
“…The complete inactivation of bacteria in -Ag/rGO NC was also carried out to distinguish the bacterial inactivation caused by the physical contact from that caused by the photocatalytic process. 38 The log reduction of only 1.5 in 60 min during the dark control experiment clearly states that the bacterial inactivation is actually a photocatalytic process and not just due to physical contact with NC. The enhanced photocatalytic properties of ZnFe 2 O 4 -Ag/rGO as compared to those of ZnFe 2 O 4 and ZnFe 2 O 4 /rGO can be attributed to the increased surface area and better charge generation and separation due to the presence of rGO and Ag NPs.…”
Section: Resultsmentioning
confidence: 87%